Pengaruh pembiayaan produktif mudharabah perbankan syariah terhadap pertumbuhan ekonomi Provinsi Jambi - Dedi Afriyandi F; Amri Amir; Ridwan Ridwan (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2020)
This study aims to analyze the trend of productive financing of Islamic banking mudharabah in Jambi Province, to analyze the dominant productive financing of mudharabah from Islamic banking in Jambi Province, and to analyze the effect of productive financing of Islamic banking mudharabah on economic growth in Jambi Province. This research uses descriptive and quantitative analysis methods. Based on the results of the analysis of trends in the development of productive financing of mudharabah banking, Jambi Province quarterly during 2010-2014 was included in the positive category, and the most dominant mudharabah productive financing in Jambi Province for the quarterly during 2010-2014 was working capital financing and during 2010-2014 productive mudharabah has a significant and positive effect on economic growth in Jambi Province. Keywords: Productive financing the sharia banking, Economic growth